United States : Publication of Financial Sector Assessment Program Documentation; Technical Note on Selected Issues on Liquidity Risk Management in Fedwire Funds and Private Sector Payment. (IMF Staff Country Reports; Country Report ;, 2010)
This paper discusses Selected Issues on Liquidity Risk Management in Fedwire Funds and Private Sector Payment for the United States. While an asymmetric treatment of foreign banking organizations exists regarding the calculation of the capital measure for caps and the fee deductible, policy provisions implemented in March 2009 substantially addressed this asymmetry. Steps are needed to amend Fedwire's settlement procedures for tri-party repo transactions, Depository Trust Company, and Clearing House Interbank Payments System to discourage late-in-the-day payments.